2013
DOI: 10.1242/jcs.134551
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease/angiogenin inhibitor 1 regulates stress-induced subcellular localization of angiogenin and controls its growth and survival activities

Abstract: SummaryAngiogenin (ANG) promotes cell growth and survival. Under growth conditions, ANG undergoes nuclear translocation and accumulates in the nucleolus where it stimulates rRNA transcription. When cells are stressed, ANG mediates the production of tRNA-derived stressinduced small RNA (tiRNA), which reprograms protein translation into a survival mechanism. The ribonucleolytic activity of ANG is essential for both processes but how this activity is regulated is unknown. We report here that ribonuclease/angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 55 publications
2
114
0
6
Order By: Relevance
“…S7B). These results suggest that SHOT-RNA generation may not be regulated by RNH1, in contrast to the case of tiRNAs, where the quantitative changes in RNH1 regulate expression (29).…”
Section: Abundant Accumulation Of Trna Halves In Specific Breast Andmentioning
confidence: 77%
“…S7B). These results suggest that SHOT-RNA generation may not be regulated by RNH1, in contrast to the case of tiRNAs, where the quantitative changes in RNH1 regulate expression (29).…”
Section: Abundant Accumulation Of Trna Halves In Specific Breast Andmentioning
confidence: 77%
“…The mechanism by which ER stress promotes ANG-RNH1 dissociation is not known, but might involve RNH1 nuclear translocation. 29 In parallel, during ER stress ANG mRNA expression increases under the control of the IRE1a-XBP1 axis, as well as protein level, albeit to a lesser extent, maybe because the protein is in part secreted. Newly produced ANG is also involved in cytoprotection, and we cannot exclude that ANG has cytoprotective properties independent of tiRNA production.…”
Section: Discussionmentioning
confidence: 98%
“…We first analyzed the interaction of ANG and the ribonuclease inhibitor ribonuclease/angiogenin inhibitor 1 (RNH1), an important regulator of ANG activity, whose dissociation under stress is required to allow ANG cellular activity. 29 Co-immunoprecipitation analysis revealed that the association of ANG and RNH1 was disrupted following 2 hours of exposure to tunicamycin ( Figure 4A), thus indicating that ER stress promotes the release of ANG from its inhibitor. Recent findings also indicate that during stress, ANG participates in the production of stress granules (SG).…”
Section: Ang Participates In Translation Inhibition During Er Stressmentioning
confidence: 99%
“…Cellular ANG is bound to RNH1, which prevents random cleavage of cellular RNA. It has also been reported that RNH1 regulates the subcellular localization of ANG to control growth and survival [50]. To date, a total of 19 unique ANG-interacting proteins have been reported with experimental evidence ( Table 2).…”
Section: Ang-interacting Proteinsmentioning
confidence: 98%